2009
DOI: 10.1590/s0103-64402009000100009
|View full text |Cite
|
Sign up to set email alerts
|

Compressive strength of esthetic restorative materials polymerized with quartz-tungsten-halogen light and blue LED

Abstract: This study compared the compressive strength of a composite resin and compomer photoactivated with a conventional quartz-tungsten halogen-light (XL 3000, 3M/SPE) and a blue light-emitting diode (LED) (SmartLite PS; Dentsply/De Trey). Forty disc-shaped specimens were prepared using a split polytetrafluoroethylene matrix (4.0 mm diameter x 8.0 mm hight) in which the materials were inserted incrementally. The curing time of each increment was of 40 s with the QTH and 10 s with the LED. The specimens were randomly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 18 publications
(23 reference statements)
1
17
0
3
Order By: Relevance
“…A compressive study was performed by Dias and Silva (18), the authors found that the composite resin light-cured with either a halogen lamp or a LED source was similar. However, it may be speculated that the high radiation emitted by the LED in short exposure duration, accelerates the curing reaction, reducing the polymer flowability, increasing the modulus of elasticity and shortening the pre-gel phase, which could interfere with the results of resistance to compression.…”
Section: Discussionmentioning
confidence: 99%
“…A compressive study was performed by Dias and Silva (18), the authors found that the composite resin light-cured with either a halogen lamp or a LED source was similar. However, it may be speculated that the high radiation emitted by the LED in short exposure duration, accelerates the curing reaction, reducing the polymer flowability, increasing the modulus of elasticity and shortening the pre-gel phase, which could interfere with the results of resistance to compression.…”
Section: Discussionmentioning
confidence: 99%
“…Silva CM et al 14 concluded that the compressive strength of the composite resin light-cured with either a halogen lamp or a LED source was similar.…”
Section: Discussionmentioning
confidence: 99%
“…Contrary to the paper by Yüzügüllü et al (2008), outcomes indicate that the compressive strengths of resin-composite fi lling materials are less than dental amalgam, showing the lowest physical properties in the microfi lled hybrid materials, whereas all other groups (hybrid, nano-hybrid, packable and ormocer) were not signifi cantly different. They concluded that most categories of resin composite, except the microfi lled materials, can be regarded as being suitable for loading in posterior restorations, but care is needed for large restorations and for those patients that show © Woodhead Publishing Limited, 2013 Bryant (1979); Combe et al (1999); el-Kalla and Garcia-Godoy (1999); Xie et al (2000); Peez and Frank (2006); Craig (1997), Yüzügüllü et al (2008); Ilie and Hickel (2009); Silva and Dias (2009). occlusal functional habits such as bruxism. It is known that microfi lled materials tend to chip more easily than 'conventional' composite materials (Lambrechts et al, 1982) and therefore should not be used in load bearing restorations.…”
Section: Physical Propertiesmentioning
confidence: 99%